2015
DOI: 10.1016/j.jsat.2014.10.004
|View full text |Cite
|
Sign up to set email alerts
|

African American cocaine users' preferred treatment site: variations by rural/urban residence, stigma, and treatment effectiveness

Abstract: To encourage access, policy makers and providers need information about variations in drug users’ treatment preferences. This study examined how rural/urban residence, stigma surrounding drug use, and perceived treatment availability and effectiveness are associated with African American cocaine users’ preferences for the site of treatment (local, or in one’s home town; nearby, or in a town nearby; and distant, or in a town farther away). Two hundred rural and 200 urban cocaine users were recruited using Respo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 29 publications
(37 reference statements)
0
13
0
Order By: Relevance
“…Exactly why fewer rural people who use cocaine find HIV testing sites as acceptable remains unclear, but we posit that it could be explained by doubts about the need for HIV testing, stigma associated with getting tested, and concern about the confidentiality of testing results, which were cited as barriers to HIV testing in a qualitative research study conducted among rural AAs using cocaine in Arkansas (42). In related research, we found that worse perceptions of the effectiveness of local substance use treatment was negatively associated with a preference to seek local over non-local substance use treatment (43). Similarly, perceptions of the accessibility and availability of HIV testing locations may contribute to perceptions of their acceptability.…”
Section: Discussionmentioning
confidence: 99%
“…Exactly why fewer rural people who use cocaine find HIV testing sites as acceptable remains unclear, but we posit that it could be explained by doubts about the need for HIV testing, stigma associated with getting tested, and concern about the confidentiality of testing results, which were cited as barriers to HIV testing in a qualitative research study conducted among rural AAs using cocaine in Arkansas (42). In related research, we found that worse perceptions of the effectiveness of local substance use treatment was negatively associated with a preference to seek local over non-local substance use treatment (43). Similarly, perceptions of the accessibility and availability of HIV testing locations may contribute to perceptions of their acceptability.…”
Section: Discussionmentioning
confidence: 99%
“…Briefly, data presented in this manuscript were collected during phase 1 of a sequential, mixed-methods study among African American cocaine users’ perceived need for drug treatment and HIV tests (Booth, Stewart, Curran, Cheney, & Borders, 2014; Borders et al, 2014; Borders, Booth, Stewart, Cheney, & Curran, 2015). Semi-structured interviews were conducted with 51 African American cocaine users between 2010 and 2012.…”
Section: Methodsmentioning
confidence: 99%
“…Studies in southern states indicate increasing availability of stimulants, particularly methamphetamine (Booth, Luekfeld, Falck, Wang, & Carlson, 2006) and cocaine (Borders, Booth, & Curran, 2015). We sought to qualitatively explore the relationships between ongoing involvement in the criminal justice system and continued drug use in a population of urban and rural African American cocaine users in a southern state.…”
mentioning
confidence: 99%
“…The majority of stimulant users do not seek substance use treatment (Curran et al 2011). Given this context, it is unclear how age group is associated with use of services for physical and mental health problems among stimulant users, and particularly among those living in rural areas having reduced access to health care services (Borders et al 2015;Goins et al 2005). Data suggest that stimulant users use hospital resources at higher rates than the average emergency department population, and that they are more likely to be admitted when they present to the emergency department for treatment (Richards et al 1999), though this research is not informative as to age group of stimulant users.…”
Section: Association Of Age Group With Health and Treatment Utilizationmentioning
confidence: 99%
“…Most research on stimulant use has focused on younger users, yielding little knowledge regarding stimulant use among older adults, especially those living in rural areas. Stimulant use is a critical problem in rural areas (Grant et al 2007), and is compounded by more barriers to health care in rural compared to urban regions (Borders et al 2015;Goins et al 2005;Weeks et al 2004). Older adults often need more health care than younger adults due to an increase in agerelated medical conditions (Kessler et al 2010), though it is unclear whether these age-related differences in health outcomes and health care utilization hold among rural adults who use stimulants.…”
Section: Introductionmentioning
confidence: 99%